Rhetorical Adaptation in the Greek Historians, Josephus, and Acts vol II : Embedded Speeches, Audience Responses, and Authorial Persuasion - Duncan, John M. (Biblical Interpretation Series, 2022)
A detailed comparative analysis of speaker-audience interactions in Greek historiography, Josephus, and Acts that examines historians' use of speeches as a means of instructing/persuading their readers and highlights Luke's distinctive depiction of the apostles as adaptable yet frequently alienating orators.